Biomolecular interactions of small-molecule inhibitors affecting the YopH protein tyrosine phosphatase - Hogan, Megan (2013)
We have developed competitive and direct binding methods to examine small-molecule inhibitors of protein tyrosine phosphatase (PTPase) activity. Focusing on the Yersinia outer protein H (YopH), a potent bacterial PTPase, we describe how an understanding of the kinetic interactions involving YopH, peptide substrates, and small-molecule inhibitors of PTPase activity can be beneficial for inhibitor screening and we further translate these results into a microarray assay for high-throughput screening.